Compound hydrometeorological extremes across multiple timescales drive volatility in California electricity market prices and emissions. (15th October 2020) - Su, Yufei; Kern, Jordan D.; Reed, Patrick M.; Characklis, Gregory W.
Highlights: Hydrometeorological variables drive prices and emissions on California's grid. Time scale controls which combination of variables exert the greatest influence. Market prices appear most sensitive to periods of extreme abundance (over supply) Historical data severely underrepresents the occurrence of these low price events. Abstract: Hydrometeorological conditions influence the operations of bulk electric power systems and wholesale markets for electricity. Streamflow is the "fuel" for hydropower generation, wind speeds and solar irradiance dictate the availability of wind and solar power production, and air temperatures strongly affect heating and cooling demands. Despite growing concern about the vulnerability of power systems to hydrometeorological uncertainty, including "compound" extremes (multiple extremes occurring simultaneously), quantifying baseline probabilistic risks remains difficult even without factoring in climate change. Here, we use newly developed power system simulation software to show how uncertainties in spatially and temporally correlated hydrometeorological processes affect market prices and greenhouse gas emissions in California's wholesale electricity market. Results highlight the need for large synthetic datasets to access rare, yet plausible system states that have not occurred in the recent historical record. We find that time scale strongly controls which combinations of hydrometeorological variables cause extreme outcomes. Although scarcity caused by low streamflows and high air temperatures has long been considered a primary concern in Western power markets, market prices are more profoundly impacted by weather and streamflow conditions that lead to an overabundance of energy on the grid.